Recycled Ceramics in Sustainable Concrete Properties and Performance - Shah, Kwok Wei; Huseien, Ghasan Fahim (Boca Raton : CRC Press, 2020)
Recycled Ceramics in Sustainable Concrete: Properties and Performance explores the use of novel waste materials in the construction industry as sustainable and environmentally friendly alternatives to traditional cement production technologies. It specifically focuses on using waste ceramics as a binder and aggregate replacement for concrete. Includes a lifecycle assessment Describes recycling of ceramic tile waste as fine and coarse aggregate replacement Discusses microstructure performance of sustainable concrete Evaluates performance of sustainable concrete exposed to elevated temperatures and corrosives Written for materials, chemical, and civil engineers as well as others who develop construction materials, this book provides readers with a thorough understanding of the merits of using waste ceramics to produce sustainable concrete. .
OCLC-licensed vendor bibliographic record.
Keywords: Concrete -- Additives; Ceramic materials -- Recycling; TECHNOLOGY / Material Science; TECHNOLOGY / Construction / Masonry